Flexible Hot Rolling of Extruded Shapes of Aluminum Alloy EN AW-6082 - Grydin, Olexandr; Sotirov, Nikolay; Samsonenko, Andrii; Biba, Nikolay; Andreiev, Anatolii; Stolbchenko, Mykhailo; Behr, Teresa; Frolov, Iaroslav; Schaper, Mirko (Materials Science Forum)
One of the strategies employed to lower weight and to decrease material consumption is reducing part thickness itself. Thus, functionally graded materials in which structural reinforcement is adjusted locally, are of great interest. With regard to conventional industrial processes, such as extrusion or flexible cold rolling, thickness variations can only be achieved either longitudinally or through the cross-section of the semi-finished products. Hence, a combined thickness variation (along both axes) is difficult to generate solely by extrusion or rolling. A simultaneous thickness variation in both directions, however, would enable further weight savings in structural components such as car body parts. In this study, a promising approach with extruded shapes, serving as a billet for a flexible hot rolling process, is elaborated upon. By employing the described process modification, shapes with simultaneous thickness variations in longitudinal as well as in transverse direction are feasible. Initial numerical analysis reveals the weight-saving potential of using these semi-finished products for structural parts in a car body. A demonstration of the production process for the semi-finished parts and the occurring challenges are discussed. To verify and adjust the new technology, a numerical model of the flexible hot rolling process has been created based on the finite element software QForm VX. This model is also employed for tool design optimization to produce semi-finished components with the required geometrical quality. Finally, the results of hot rolling experiments conducted using the adjusted roll design are presented.

Optimization of Tooling Design for Hot Mandrel Bending of Pipe Elbows - Diekmann, Uwe; Homberg, Werner; Prehm, Jens; Rostek, Tim; Schönhoff, Nils; Tabakajew, Dmitri; Trasca, Andreea; Uysal, Haris (Materials Science Forum)
This paper presents the finite element model developed for the simulation of pipe elbow production by the so-called ‘Hamburg process’ in order to improve productivity and resource efficiency. To optimize the tooling design, a sensitivity analysis of the tool parameters that influence the quality of pipe elbows, such as mandrel height and length, is conducted. Different materials data sets including damage models were considered. Using numerical simulations, it is possible to determine an optimized tool geometry for the production of specific pipe elbow dimensions. Furthermore, as a result of the experiments and numerical simulations conducted, it is possible to increase the production velocity of the serial plant. Along with deformation, damage models are included in simulations in order to identify the right process boundaries. Finally, an experimentally validated model is developed for increasing resource efficiency in pipe elbow fabrication.

Hydrogen Effects in ECR-Etching of 3C-SiC(100) Mesa Structures - Hiller, Lars; Stauden, Thomas; Kemper, Ricarda M.; Lindner, Jörg; As, Donat J.; Pezoldt, Jörg (Materials Science Forum)
An anisotropic etching process for mesa structures using fluorinated plasma with hydrogen addition was developed in an electron cyclotron resonance setup. The evolution of the mesa morphology was studied in dependence on the gas composition, the applied bias and the pressure. The achieved side wall slope approached 90° with a negligible trenching. The aspect ratios of the fabricated structure in the developed residue free ECR plasma etching process were between 5 and 20.

ECR-Ectching of Submicron and Nanometer Sized 3C-SiC(100) Mesa Structures - Hiller, Lars; Stauden, Thomas; Kemper, Ricarda M.; Lindner, Jörg; As, Donat J.; Pezoldt, Jörg (Materials Science Forum)
Anisotropic etching processes for mesa structure formation using fluorinated plasma atmospheres in an electron cyclotron resonance (ECR) plasma etcher were studied on Novasic substrates with 10 μm thick 3C-SiC(100) grown on Si(100). To achieve reasonable etching rates, a special gas inlet system suitable for injecting SF6 into the high density downstream Ar ECR plasma was designed. The influence of the etching mask material on the sidewall morphology was investigated. Masking materials with small grain sizes are preferable to achieve a desired shape. The evolution of the mesa form was investigated in dependence on the gas composition, the applied bias, the pressure and the composition of the gas atmosphere. The achieved sidewall slope was 84.5 deg. The aspect ratios of the fabricated structures in the developed residue free ECR plasma etching process were between 5 and 10. Mesa structures aligned to [100] and [110] directions were fabricated.

Fine Structure of Triplet Centers in Room Temperature Irradiated 6H-SiC - Scholle, Andreas; Greulich-Weber, Siegmund; Rauls, Eva; Schmidt, Wolf Gero; Gerstmann, Uwe (Materials Science Forum)
In non-annealed 6H-SiC samples that were electron irradiated at room temperature, a new EPR signal due to a S=1 defect center with exceptionally large zero-field splitting (D = +652·10-4 cm-1) has been observed under illumination. A positive sign of D demonstrates that the spin-orbit contribution to the zero-field splitting exceeds by far that of the spin-spin interaction. A principal axis of the fine structure tilted by 59° against the crystal c-axis as well as the exceptionally high zero-field splitting D can be qualitatively understood by the occurrence of additional close-lying defect levels in defect clusters resulting in comparatively large second-order spin-orbit coupling. A tentative assignment to vacancy clusters is supported by the observed annealing behavior.

Fine Structure of Triplet Centers in Room Temperature Irradiated 6H-SiC - Scholle, Andreas; Greulich-Weber, Siegmund; Rauls, Eva; Schmidt, Wolf Gero; Gerstmann, Uwe (Materials Science Forum)
In non-annealed 6H-SiC samples that were electron irradiated at room temperature, a new EPR signal due to a S=1 defect center with exceptionally large zero-field splitting (D = +652•10-4 cm-1) has been observed under illumination. A positive sign of D demonstrates that the spin-orbit contribution to the zero-field splitting exceeds by far that of the spin-spin interaction. A principal axis of the fine structure tilted by 59° against the crystal c-axis as well as the exceptionally high zero-field splitting D can be qualitatively understood by the occurrence of additional close-lying defect levels in defect clusters resulting in comparatively large second-order spin-orbit coup¬ling. A tentative assignment to vacancy clusters is supported by the observed annealing behavior.

Textile Solar Cells Based on SiC Microwires - Greulich-Weber, Siegmund; Zöller, M.; Friedel, B. (Materials Science Forum)
The solar cell concept presented here is based on 3C-SiC nano- or microwires and conju¬gated polymers. Therefore the silicon carbide wires are fabricated by a sol-gel route including a car-bothermal reduction step, allowing growth with predetermined uniform diameters between 0.1 and 2μm and lengths up to several centimetres. The design of our photovoltaic device is therein based on a p-i-n structure, well known e.g. from silicon photovoltaics, involving an intrinsic semiconduc¬tor as the central photoactive layer, sandwiched between two complementary doped wide-bandgap semiconductors giving the driving force for charge separation. In our case the 3C-SiC microwires act as the electron acceptor and simultaneously as carrier material for all involved components of the photovoltaic element.

Bottom-Up Routes to Porous Silicon Carbide - Greulich-Weber, Siegmund; Friedel, B. (Materials Science Forum)
We report on constructive methods providing a large range of high purity porous SiC products. All methods are based on modified sol-gel processes combined with carbothermal re¬duction. We obtain monodisperse regular pores of well defined diameters by using carbon sphere templates which are removed after SiC infiltration. A different way is a sol-gel based conversion of graphite bodies into SiC, which transfers the porosity from the graphite matrix into the final SiC product. Thus a large variety of porosity features are available, originating either from natural poro¬sity of graphite or from priorly created nano-/ microstructures in the carbonaceous base material. Whereas all our pristine porous sol-gel derived silicon carbide products are semi-insulating, doping is possible, during the growth to modifiy the electrical and optical properties.

Spin-Coupling in Heavily Nitrogen-Doped 4H-SiC - Savchenko, D.V.; Pöppl, Andreas; Kalabukhova, Ekaterina N.; Greulich-Weber, Siegmund; Rauls, Eva; Schmidt, Wolf Gero; Gerstmann, Uwe (Materials Science Forum)
EPR and ESE in nitrogen doped 4H- and 6H-SiC show besides the well known triplet lines of 14N on quasi-cubic (Nc,k) and hexagonal (Nc,h) sites additional lines (Nx) of comparatively low intensity providing half the hf splitting of Nc,k. Frequently re-interpreted as spin-forbidden lines, arising from Nc,k pairs and triads or resulting from hopping conductivity, only recently the theoretical calculation of the corresponding g-tensors lead to a tentative model of distant NC donor pairs on inequivalent lattice sites which are coupled to S = 1 assuming a fine-structure splitting too small to be observed in the EPR and ESE experiments. In this work, we present ESE nutation measurements confirming S = 1 for the Nx center. Analysing the nutation frequencies in comparison with that of the Nc,k (S = 1/2) spectrum as well as the line width of ESE and EPR spectra we obtain a rough estimate between 5×104 cm-1 and 50×104 cm-1 for the fine-structure splitting demonstrating efficient spin-coupling between nitrogen donors in 4H-SiC.

Spin-Coupling in Heavily Nitrogen-Doped 4H-SiC - Savchenko, D.V.; Pöppl, Andreas; Kalabukhova, Ekaterina N.; Greulich-Weber, Siegmund; Rauls, Eva; Schmidt, Wolf Gero; Gerstmann, Uwe (Materials Science Forum)
EPR and ESE in nitrogen doped 4H- and 6H-SiC show besides the well known triplet lines of 14N on quasi-cubic (Nc,k) and hexagonal (Nc,h) sites additional lines (Nx) of comparatively low intensity providing half the hf splitting of Nc,k. Frequently re-interpreted as spin-forbid¬den lines, arising from Nc,k pairs and triads or resulting from hopping conductivity, only re¬cent¬ly the theoretical calculation of the corresponding g-tensors lead to a tentative model of distant NC donor pairs on inequivalent lattice sites which are coupled to S = 1 assuming a fine-struc¬ture splitting too small to be observed in the EPR and ESE experiments. In this work, we pre¬sent ESE nutation measurements confirming S = 1 for the Nx center. Analysing the nutation frequencies in comparison with that of the Nc,k (S = 1/2) spectrum as well as the line width of ESE and EPR spectra we obtain a rough estimate between 5104 cm-1 and 50104 cm-1 for the fine-structure splitting demonstrating efficient spin-coupling between nitrogen donors in 4H-SiC.

The Effect of Texture on the Fatigue Properties of Ultrafine-Grained Interstitial-Free Steel - Niendorf, Thomas; Marten, Thorsten; Maier, Hans J.; Karaman, Ibrahim (Materials Science Forum)
The present paper reports on the effect of texture on the cyclic stress-strain response (CSSR) and the fatigue life of ultrafine-grained (UFG) interstitial-free (IF) steel. Tests in the lowcycle fatigue (LCF) regime were conducted on material that was processed by the equal channel angular extrusion (ECAE) technique along the so called “efficient” route 8E. This route has been shown to result in a homogeneous microstructure with a high fraction of high angle grain boundaries (HAGBs), which are beneficial for a stable CSSR. In addition, the evolution of the microstructure was characterized by means of electron optical techniques, including electron backscattered diffraction, and by X-Ray diffractometry. It was found that the initial texture of specimens cut from the ECAE billet along different orientations with respect to the extrusion direction (ED) has a substantial effect on the CSSR of the UFG IF steel. Furthermore, microscopy results indicated the notable influence of the last ECAE processing step on the evolution of damage in the material.

A High Resolution Investigation of the Anisotropic Electron-Positron Momentum Distribution in Diamond - Nilen, R.W.N.; Connell, S.H.; Britton, D.T.; Fischer, C.G.; Sendezera, E.J.; Schmidt, Wolf Gero; Sellschop, J.P.F.; Verwoerd, W.S. (Materials Science Forum)